ADAM15 Supports Prostate Cancer Metastasis by Modulating Tumor Cell–Endothelial Cell Interaction - Najy, Abdo J.; Day, Kathleen C.; Day, Mark L. (Cancer research (Chicago, Ill.), 2008)
Using human tumor and cDNA microarray technology, we have recently shown that the ADAM15 disintegrin is significantly overexpressed during the metastatic progression of human prostate cancer. In the current study, we used lentiviral-based short hairpin RNA (shRNA) technology to down-regulate ADAM15 in the metastatic prostate cancer cell line, PC-3. ADAM15 down-regulation dramatically attenuated many of the malignant characteristics of PC-3 cells in vitro and prevented the s.c. growth of PC-3 cells in severe combined immunodeficient (SCID) mice. By inhibiting the expression of ADAM15 in PC-3 cells, we showed decreased cell migration and adhesion to specific extracellular matrix proteins. This was accompanied by a reduction in the cleavage of N-cadherin by ADAM15 at the cell surface. Fluorescence-activated cell sorting analysis revealed reduced cell surface expression of the metastasis-associated proteins αv integrin and CD44. Furthermore, matrix metalloproteinase 9 secretion and activity were abrogated in response to ADAM15 reduction. In an in vitro model of vascular invasion, loss of ADAM15 reduced PC-3 adhesion to, and migration through, vascular endothelial cell monolayers. Using an SCID mouse model of human prostate cancer metastasis, we found that the loss of ADAM15 significantly attenuated the metastatic spread of PC-3 cells to bone. Taken together, these data strongly support a functional role for ADAM15 in prostate tumor cell interaction with vascular endothelium and the metastatic progression of human prostate cancer. [Cancer Res 2008;68(4):1092–9]